The Relationship among Retail Store Environment, Customer Satisfaction and Customer Loyalty in Convenience Store (Case Study of Indomaret & Alfamart Customer in Malang City, Indonesia) - Fajrianto, Jozarky (Jurnal Ilmiah Mahasiswa FEB, 2015)
The development of globalization era encourages the emergence of several new retail business followed by the rapid growth of technology, competition and changes of the business environment. Indonesian consumers prefer to shop at modern market, which is clean,    comfortable,   quiet, and has a good layout rather than shopping at traditional market. The retail store environment is one of the important things that must continue to be improved and made as attractive as possible in order to provide a sense of satisfaction to customers, which will be able to create a sense of customer loyalty to the visited retail market.This research aims to determine the relationship among retail store environment, customer satisfaction, and customer loyalty on Indomaret and Alfamart customer in Malang City. The data analysis in this research using SEM (Structural Equation Model) Method with 100 consumers who shopped at Indomaret and Alfamart as respondents. The sampling technique used is purposive sampling. The data processing in this study is using LISREL (Linear Structural Relationship) 8.8 software which is the statistical software package for SEM.In this research it is indicated that the retail store environment has indirect significant influence on customer loyalty through customer satisfaction on Indomaret and Alfamart customer in Malang City. By maintaining and improving retail store environment which comfortable, neat and orderly displayed, then the consumers who shop at Indomaret and Alfamart will be satisfied. When the customers feel satisfied while shopping then the sense of loyalty towards Indomaret and Alfamart will appear automatically so Indomaret and Alfamart customers will be hard to move to other similar shopping places. Therefore, Indomaret and Alfamart become main retail market of consumer.Key Word:  Indomaret,  Alfamart,  retail  store environment,  customer satisfaction, customer loyalty